Association between serum albumin levels and erectile dysfunction in American Adults: A cross-sectional study from NHANES 2001-2004. - Haibin Wen; Zhenyu Lan; Xueming Liang; Huabin Su; Yuqi Qin (PLoS ONE)
Background The aim of this study is to investigate the association between Serum Albumin Levels (ALB) and erectile dysfunction (ED) within the U.S. general population. Methods We conducted a cross-sectional analysis using data from the National Health and Nutrition Examination Survey (NHANES) 2001-2004 cycles. Serum albumin was analyzed both as a continuous variable and categorized into quartiles. Erectile dysfunction (ED) was assessed via self-reported questionnaires. The association between serum albumin and erectile dysfunction was evaluated using weighted logistic regression models across four models: (1) Crude model (unadjusted); (2) Model 1: Adjusted for age, race, poverty-to-income ratio (PIR), marital status, education level, and body mass index (BMI); (3) Model 2: Adjusted for factors in Model 1 plus physical activity, smoking status, drinking status, and Healthy Eating Index (HEI-2015); (4) Model 3: Adjusted for factors in Model 2 plus remaining potential covariates. A generalized additive model (GAM) was employed to examine non-linear associations, followed by subgroup analyses and interaction tests. Results A total of 2925 participants were included in the study, of which 747 were diagnosed with ED. After adjusting for all covariates, a significant negative association was found between ALB and ED (OR: 0.53, 95% CI: 0.29-0.97, P = 0.04). Higher ALB quartiles were significantly correlated with a decreased risk of ED [Q4 vs. Q1: OR: 0.56 (0.35-0.90), P =  0.02; P for trend =  0.03]. The GAM and smoothed curve fit indicated a linear relationship between ALB and the risk of ED. Stratified and interaction tests further substantiated the inverse relationship between ALB and ED prevalence. Conclusions This study revealed an inverse association between ALB and ED. Therefore, it is important for clinicians to recognize the assessment of ALB in patients.